Developing virtual campus tour using panoramic video / Nur Izlin Iskak - Iskak, Nur Izlin (2020)
Difficulty in finding the destination is a common problem faced by students, staffs and visitors of a university. To solve the problem, the virtual campus tour is a recommended technology that can be implemented in a university website. The virtual campus tour which can be accessed as mobile app or website, can help its users in their journey around campus. Furthermore, it can save time. Agile method was used as the development technology. It has four phases, requirement phase, design phase, development phase and test feedback phase. In this virtual campus tour, features that user can use are hotspot of main building such as academic building, college and administration building. The virtual campus tour was develop in panoramic video where user can see in 360-degree view of campus area. Based on preliminary investigation conducted via online form, it was discovered that 60.9% of the respondent come from students and 39.1% respondent from visitors of university. In the online form, the respondents need to answer six questions, such as on how they find a particular destination within university campus, did they ever lost their way when finding a destination in campus area and what features that they prefer if virtual campus tour is develop. User Acceptance Testing (UAT) was conducted to ensure the virtual campus tour is accepted by user. From the User Acceptance Testing (UAT), 19 from the respondents strongly agree that Virtual Campus Tour makes them easier to find a building while 11 of them agree. Besides that, this Virtual Campus Tour web-based system that using panoramic video is useful for anyone who visits UiTM Perlis that most of the respondents strongly agree. Then, it is recorded that 12 respondents strongly agree that they tend to use Virtual Campus Tour web-based system in the future and they will recommend Virtual Campus Tour to their family, friends and other visitors. In Heuristic Evaluation, five experts were chosen to testing the system. The experts comments about the design of the web-based system and the panoramic video for virtual campus tour.